Behavior of “Intermediate” Males of the Dimorphic Squid Doryteuthis pleii Supports an Ontogenetic Expression of Alternative Phenotypes - Apostólico, Lígia H.; Marian, José E. A. R. (Frontiers in Physiology, 2019)
The expression of alternative reproductive tactics (ARTs) by different-sized males of loliginid squids has been extensively investigated. In loliginids, alternative phenotypes are characterized by differences in behavior, body size, sperm deposition site, and morphology and functioning of ejaculates. Consort males guard females, display agonistic behaviors towards rival males, and mate with females in male-parallel position (MP). Sneaker males avoid fights and instead adopt furtive behaviors to access females guarded by consort males, mating in the head-to-head posture (HH). Recently, reappraisal of preserved material from the loliginid squid Doryteuthis pleii showed that intermediate-sized males (so-called “intermediate” males) had both sneaker- and consort- like ejaculates, leading to the hypothesis of them being a transitional stage between both phenotypes. Here, we describe observations made in captivity showing that intermediate males can display agonistic behaviors towards consort males and mate with females in both mating positions, depending on the male’s current reproductive context, i.e., generally in HH, but switching to MP when the female is laying eggs. Such unusual findings of intermediate males simultaneously displaying behaviors of both sneaker and consort males comprise additional evidence corroborating the ontogenetic hypothesis for phenotypic expression of ARTs in this species. Taken together, our results indicate that (1) instead of competing with large consort males for female access and monopolization, small/young males adopt sneaker tactics to obtain mating opportunities, and (2) as they continue to grow, they gradually modify the morphology of their ejaculates and their mating behavior, going through an “intermediate” stage, before becoming large consort males.